The trap game: neoliberal governmentalities and the origins of Southern hip-hop - Knight, James (2021)
Great deals of scholarship centred on American hip-hop tend to assert its position as one of contrary to the system. It is usually posited as a site of collective representation of the United States’ most disadvantaged people, and as one that is seemingly at odds with the American neoliberal system. Those that have touched upon neoliberal elements within hip-hop have focussed on either hip-hop from the East Coast and New York, or on gangsta-rap on the west coast in Los Angeles. This thesis will argue that the hip-hop south is worthy of a great deal of attention as a site for which to analyse neoliberal governmentalities as a key component of hip-hop. It will show that neoliberal governance internalises neoliberal values through a simultaneous appeal to freedom and threat of loss to personal control, which results in a form of neoliberal “reactance” to immediate environmental pressures. It will further assert that hip-hop does not always necessarily represent the great spirit of collective identity that stands in opposition to the American government, but rather uses collective identity as a key component in its authenticity and by proxy its market value. The music still retains elements of social protest against the neoliberal system of governance, yet remains tied to neoliberal values.